C-reactive protein-to-albumin ratio predicts intensive care admission and disease severity in autoimmune encephalitis - Zhang, Lin-Jie; Han, Zewen; Shao, Ying-Zhe; Zhang, Qiu-Xia; Zhao, Ning; Xu, Xiao-Yi; Yang, Li (Frontiers in Immunology, 2026)
ObjectiveTo evaluate the clinical relevance of the C-reactive protein/albumin ratio (CAR) in patients with autoimmune encephalitis (AE), with an emphasis on its predictive utility for disease severity, intensive care unit (ICU) admission, and functional outcomes.MethodsA retrospective cohort of 114 patients with AE was analyzed. Serum C-reactive protein (CRP) and albumin (ALB) levels were measured within 24 hours of admission, and CAR was subsequently calculated. Disease severity was assessed using the Clinical Assessment Scale for Autoimmune Encephalitis (CASE) and the modified Rankin Scale (mRS) at discharge. Statistical analyses included the Mann–Whitney U test, Spearman correlation, logistic regression, and receiver operating characteristic (ROC) curve analysis to evaluate associations with ICU admission, respiratory failure, and disability.ResultsPatients requiring ICU admission exhibited significantly elevated CRP levels (11.00 vs. 2.40 mg/L, p < 0.001), reduced ALB levels (36.00 vs. 38.00 g/L, p = 0.029), and higher CAR values (0.282 vs. 0.064, p < 0.001). Comparable patterns were observed in patients with respiratory failure and severe disability (mRS ≥ 3). CAR demonstrated stronger correlations with both CASE score at admission (r = 0.448, p < 0.001) and mRS at discharge (r = 0.222, p = 0.018) than either CRP or ALB alone. Multivariate logistic regression analysis, adjusted for age, sex, CASE score, and other potential confounders, identified CAR (OR = 2.100; 95% CI: 1.151–3.831; p = 0.016), CRP (OR = 1.023; 95% CI: 1.004–1.042; p = 0.015), and ALB (OR = 0.875; 95% CI: 0.787–0.973; p = 0.013) as independent predictors of ICU admission. ROC curve analysis indicated high predictive accuracy for CAR (AUC = 0.835; cutoff = 0.125; sensitivity = 91.3%) and CRP (AUC = 0.820; cutoff = 4.35; sensitivity = 82.6%).ConclusionCAR represents a novel and readily accessible biomarker that outperforms CRP or ALB alone in predicting disease severity and the need for ICU care in patients with AE. Its incorporation into early clinical assessment protocols may enhance risk stratification and inform decisions regarding intensive care resource allocation.